2021
DOI: 10.3389/fped.2021.638871
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Maternal Immunization in Early Life

Abstract: With birth, the newborn is transferred from a quasi-sterile environment to the outside world. At this time, the neonatal immune system is inexperienced and continuously subject to a process of development as it encounters different antigenic stimuli after birth. It is initially characterized by a bias toward T helper 2 phenotype, reduced T helper 1, and cytotoxic responses to microbial stimuli, low levels of memory, and effector T and B cells and a high production of suppressive T regulatory cells. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 167 publications
(205 reference statements)
0
25
0
Order By: Relevance
“…Neonate vaccination could be affected by maternal antibodies [6], whereas neonatal DNA vaccination seems to overcome the inhibitory effect of maternal immunization, favoring neonatal antigen priming. At the site of injection, DNA vaccines delivered to cells mainly induce a CD8+ T-cell response [7].…”
Section: Introductionmentioning
confidence: 99%
“…Neonate vaccination could be affected by maternal antibodies [6], whereas neonatal DNA vaccination seems to overcome the inhibitory effect of maternal immunization, favoring neonatal antigen priming. At the site of injection, DNA vaccines delivered to cells mainly induce a CD8+ T-cell response [7].…”
Section: Introductionmentioning
confidence: 99%
“…7 During the first weeks after birth, the infant is therefore passively protected by maternal immunoglobulins transferred via the placenta during the last trimester of pregnancy. 8 Passive protection continues after birth, with breastmilk containing maternal secretory immunoglobulin A (sIgA) antibodies mostly derived from the respiratory and intestinal maternal mucosal immune system. 9 Specific SARS-CoV-2 maternal antibodies are transferred through the placenta during the last months of pregnancy and can be detected in the serum of the neonates born to naturally infected or vaccinated mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the protective role of breastmilk in women vaccinated during pregnancy identified a high amount of vaccine-specific sIgA in the breastmilk samples up to several weeks postpartum. [27][28][29] Consequently, a lower incidence of respiratory illness with fever episodes in young infants of influenza-vaccinated mothers was reported. 28,29 The potential of neonatal immunization against Gram-negative bacteria has also been described, either a maternal vaccination to pregnant woman, via breastmilk and directly to the neonate.…”
Section: Maternal Immunizationmentioning
confidence: 99%
“…[27][28][29] Consequently, a lower incidence of respiratory illness with fever episodes in young infants of influenza-vaccinated mothers was reported. 28,29 The potential of neonatal immunization against Gram-negative bacteria has also been described, either a maternal vaccination to pregnant woman, via breastmilk and directly to the neonate. 30 Knowledge gaps and opportunities for future research.…”
Section: Maternal Immunizationmentioning
confidence: 99%